ANALISIS FAKTOR FAKTOR YANG MEMENGARUHI MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI BAJANGREJO - Rofidatul Marfufah, Mei; Putro Widoyoko, Eko; Nurhidayati, Nurhidayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to: (1) identify the factors that influence student motivation in mathematics in grade V at Bajangrejo Public Elementary School and (2) identify the efforts made to increase student motivation in mathematics in grade V at Bajangrejo Public Elementary School. The research method used in this study was qualitative descriptive. The subjects of this study were fifth-grade teachers and fifth-grade students at Bajangrejo State Elementary School, totaling 14 students, who were then divided into three groups, namely high, medium, and low, according to the students’ abilities based on their summative assessment scores. Three samples were then taken using stratified random sampling. Data collection techniques used observation, interviews, and document analysis. The results of the discussion led to the following conclusions: (1) the factors that influence student learning motivation in mathematics in grade 5 at Bajangrejo State Elementary School are divided into two factors, namely internal factors and external factors. Internal factors consist of interest and curiosity, self-ability, physical and mental conditions. External factors consist of parental support, the role of teachers, the learning environment, and rewards. (2) Efforts that can be made to increase student motivation in learning mathematics in grade 5 at Bajangrejo Public Elementary School can be divided into two categories: efforts by teachers in the learning process and the role of parents. From the results of observations and interviews, data was obtained from the three students sampled, revealing several common factors that influence motivation in learning mathematics, namely self-ability, the role of teachers, and the learning environment.